Vivere per contarla. Le nuove scienze della scrittura e la fenomenologia della scrittura di calcolo - Masi, Felice (Mechane, 2024)
Since the 1990s, writing studies have undergone a concrete turn, focusing on the manipulation of material symbols and the links between writing and calculation. On the other hand, the claim that Husserl had an idea of language as calculus has not produced a revision of his conception of writing. I intend to propose a neo-Husserlian analysis of writing as a cognitive function of computation. The essay will thus be divided into four parts. In the first, I will outline the reasons for a neo-Husserlian supplement to the science of writing. In the second part, I will present the main results that archaeological investigations, psychological-cognitive analyses, philosophy of mathematical practice and philosophy of mediality have achieved on writing. In the third part, I will schematically present the Husserlian definitions of counting, operation, calculation, symbolic writing and reading. In the fourth part, I will show the different uses of writing for the achievement of the evidence of clarity and the evidence of distinction and why the latter is also could be defined as computational evidence.